Is There a Role for Daratumumab Retreatment in Patients with Relapsed/Refractory Multiple Myeloma? - Davor Galusic; Ivan Krecak; Viktor Blaslov; Andela Krstulovic Opara; Toni Valkovic; Sandra Basic Kinda (Biomedicines)
Multiple myeloma (MM) is a hematologic disease characterized by the clonal expansion of malignant plasma cells that accumulate in the bone marrow, leading to osteolytic bone disease, hypercalcemia, anemia, and renal dysfunction. Daratumumab was the first monoclonal anti-CD38 antibody approved for the treatment of MM, initially in relapse/refractory settings and, more recently, for newly diagnosed patients. Increased first-line usage of daratumumab will also substantially change treatment approaches for patients with relapsed/refractory disease. Due to the cost and availability of bispecific T cell redirecting antibodies (BsAbs) and chimeric antigen receptor T cell therapy (CAR-T) in real-life settings in many countries, retreatment with daratumumab in subsequent lines of therapy might be a reasonable choice. Data regarding efficacy and optimal combinations of daratumumab retreatment are lacking, and here we provide a short literature review of available data. We identified only a small number of articles based on retrospective analysis of medical records in real-life settings. A strong consistency in results regarding response rates and treatment duration was noticed among mainly heavily pre-treated MM patients, with approximately half of patients achieving at least partial remission (PR) after retreatment with daratumumab-based protocol. The duration of treatment and time to the next treatment for retreatment episodes were considerable and consistent with clinical expectations for later lines of therapy. The analysis of data in this literature review indicates that daratumumab retreatment may provide meaningful clinical benefit to some patients with relapsed/refractory MM despite having prior exposure. However, further research is needed to identify clinical and biological parameters that may predict favorable responses to daratumumab retreatment.